Convergence and Stability of New Approximation Algorithms for Certain Contractive-Type Mappings - Imo Kalu Agwu; Donatus Ikechi Igbokwe (European Journal of Mathematical Analysis, 2021)
We present new fixed points algorithms called multistep H-iterative scheme and multistep SH-iterative scheme. Under certain contractive-type condition, convergence and stability results were established without any imposition of the ’sum conditions’, which to a large extent make some existing iterative schemes so far studied by other authors in this direction practically inefficient. Our results complement and improve some recent results in literature.